Analisis Pengaruh Media Sosial Dalam Strategi Pemasaran Produk Usaha Mikro Kecil dan Menengah (UMKM) di Kota Tebing Tinggi - Asnahwati Asnahwati; Benny Erickson Hamonangan Hutajulu; Tara Bunga Simanungkalit (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2025)
This study aims to analyze the influence of social media usage on the effectiveness of MSME marketing strategies in Tebing Tinggi City, as well as to identify the obstacles faced by business actors and the forms of support needed to ensure optimal and sustainable use of social media. The research approach used was a qualitative case study design. Data were collected through in-depth interviews, observation, and documentation of MSME actors who actively use social media. Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing, with data validity strengthened through source triangulation and member checking. The results show that social media has become a primary promotional tool for MSMEs due to its ease of use, low cost, and broad market reach. Consistent use of social media has been shown to increase the effectiveness of marketing strategies, particularly in strengthening brand identity, increasing visibility, expanding market segmentation, and building interactive relationships with consumers.